Learning and Behavioral Spillovers of Nutritional Information - Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
This paper provides evidence for informational spillovers within urban slums in Chandigarh, India. I identify three groups, a treatment group, a neighboring spillover group, and a non-adjacent pure control group. Mothers of children (aged 3-6 years) enrolled in government day-care centers are given recipe books in the treatment group to reduce malnutrition in their children. Spillovers to neighboring (untreated) mothers can be through social learning or imitation. Results from a difference-in-differences analysis show that nutritional knowledge measured through a quiz increases among neighboring untreated mothers relative to a control group. Neighboring mothers exhibit learning spillovers, changes in dietary behavior and a reduction in food expenditure regardless of their level of literacy. Spillovers not only raise the cost effectiveness of health information programs but are important to consider when designing an experiment as causal effects of treatments can be attenuated if the spillover group is used as a control group.
Keywords: D62; D83; I15; I18; I38; 330; spillovers; malnutrition; India